Ronjhangan Music in Prajekan District, Bondowoso Regency in the Context of Cultural Diffusion - Faradiba, Fani (Repertoar, 2025)
This research aims to discover the process of cultural diffusion in Ronjhangan music in Prajekan District, Bondowoso Regency. This research uses a descriptive qualitative research design with an ethnomusicological disciplinary approach that emphasises the study of text and context and is assisted by social science, which is complemented by observation, interviews, documentation, and literature studies. The data analysis techniques in this research include data reduction, presentation, and conclusion drawing. After that, the source triangulation and technique triangulation methods were used to test the validity of the data. The research shows that the arrival of Madura people to Java caused cultural diffusion that gave rise to Ronjhangan music. The dominance of Madura culture affected the Javanese population through the habits and culture brought by the Madura; besides that, many Madura people settled both temporarily and permanently in Java. The language and songs played in Ronjhangan music use the Madura language.